2010
DOI: 10.1364/oe.18.004867
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate monitoring via remote photoplethysmography with motion artifacts reduction

Abstract: In this paper, we present a novel photoplethysmographic device that operates remotely, i.e. not in contact with the skin. The device allows for real time measurements of heart rate with motion artifact reduction from a distance of a few centimeters up to several meters. High mobility of users is achieved in assessment of vital body signs, such as heart rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
51
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(52 citation statements)
references
References 12 publications
1
51
0
Order By: Relevance
“…5,13 However, it assumes that signals are steady state when physiological signals are transient in nature. Hulsbusch and Blazek have shown that the uncritical use of the FT could lead to misinterpretation of perfusion PPG signals.…”
Section: Photoplethysmography Signal Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…5,13 However, it assumes that signals are steady state when physiological signals are transient in nature. Hulsbusch and Blazek have shown that the uncritical use of the FT could lead to misinterpretation of perfusion PPG signals.…”
Section: Photoplethysmography Signal Processingmentioning
confidence: 99%
“…[4][5][6]12 This drawback limits the physiological monitoring capabilities of the technique in real application environments (i.e., hospital, homecare, and sports performance assessment). In recent years, several methods, such as blind source separation, 7 Least-mean-square adaptive filtering, 13 independent component analysis (ICA), 14 and single-channel ICA (SCICA), 15 have been proposed for removal of noise from biomedical signals. The SCICA method, introduced by James and Lowe 15 and James et al 16 has proved to be a superior solution to other available techniques because of its ability to decompose a single-channel recording into its underlying components (physiological or otherwise), using only the inherent temporal information independently of the components' origin.…”
Section: Introductionmentioning
confidence: 99%
“…Fourier Transform (FT), which offers a passage from the time domain to the frequency domain, is widely utilized in conventional PPG signal processing as it straightforwardly provides fundamental information such as heart rate and respiration rate 4,13 . However, it does not allow a combination of the two domains.…”
Section: Signal Processingmentioning
confidence: 99%
“…It is therefore critical that the device penetrate deep enough to provide detection of arterial vessels in order to determine the pulsatile changes in associated volume between systole and diastole. 3,6,8,9,16,20,23,25,26 In the present study, the interaction between various light wavelengths and skin type was investigated at rest and during exercise. We hypothesized that certain wavelengths of light would provide better light reflectance across skin types represented by a greater peak in modulation.…”
mentioning
confidence: 99%